KARAKTERISTIK LAHAN PADA PERTANAMAN DUKU (Lansium Domesticum Corr) DI PROVINSI JAMBI - Hendri Purnama; Atang Sutandi; Widiatmaka Widiatmaka; Komarsa Gandasasmita (Jurnal Ilmu Tanah dan Lingkungan, 2010)
Duku is one of horticultural crops and tropical fruits that has high commercial value. Government of Jambi Province intends to maintain and develop duku through crop improvements and extensification. For that purpose it needs to understand crop requirement related to land characteristic. The aims of this research were to identify land characteristics that associated to duku productivity, describe the optimum land characteristics to support maximum duku productivity, and to investigate the significance influence of land characteristics on optimum duku productivity. The study used primary and secondary data. Primary data was collected through field surveys, including biophysical properties and crop productivity. Secondary data included climate and duku distribution in Jambi Province. Data analysis were used line boundary method analysis and discriminant analysis. Biophysical properties and productivity were plotted on scatter diagram and the distribution of points form a model of the boundary line. The model of the biophysical properties and production relationship could determine land characteristics that associated with optimum productivity. The optimum productivity was associated with soil texture of sandy clay, sandy clay loam, loam, and clay loam, soil depth > 56 cm, soil pH between 4.5 to 6.4, C organic content > 0.60%, CEC was > 16.0 cmol kg-1, base saturation was > 5%, available P was > 1.50 ppm, exchangeable K content > 0.50 cmol kg-1, and Al saturation was < 43%. The discriminant analysis showed that the soil pH had the highest contribution on duku productivity.Key word: Boundary line, Duku, land characteristic, productivity